1998
DOI: 10.1002/hep.510270315
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1-induced vasoconstriction causes a significant increase in portal pressure of rat liver: Localized constrictive effect on the distal segment of preterminal portal venules as revealed by light and electron microscopy and serial reconstruction

Abstract: Portal hypertension is a clinical syndrome caused by a pathological increase in portal pressure usually accompanied by complications such as ascites, esophageal varices, and hepatic encephalopathy. In cirrhosis, decreased sinusoidal caliber and impaired sinusoidal wall elasticity are considered to be responsible for the increased portal pressure. [1][2][3] In addition to structural changes, humoral factors with vasoactivity may modify the resistance of portal vasculature and contribute to the pathogenesis. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 41 publications
0
52
1
Order By: Relevance
“…On the other hand, Kaneda et al demonstrated that the parenchyma of ET-1 perfused liver in rat was distinguished histologically into two areas; one consisted of loosely woven plate of vacuolated hepatocytes with widened sinusoids, and the other with closely packed hepatic cell plates intervened by narrowed, collapsed sinusoids concomitant with constriction of preterminal portal venules. 36 Increased ETBR may mediate cell contraction and increase hepatic sinusoidal microvascular tone, and contribute to portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kaneda et al demonstrated that the parenchyma of ET-1 perfused liver in rat was distinguished histologically into two areas; one consisted of loosely woven plate of vacuolated hepatocytes with widened sinusoids, and the other with closely packed hepatic cell plates intervened by narrowed, collapsed sinusoids concomitant with constriction of preterminal portal venules. 36 Increased ETBR may mediate cell contraction and increase hepatic sinusoidal microvascular tone, and contribute to portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic resistance, and thus blood flow, may be modulated at several of these sites. [3][4][5] Vascular smooth muscle cells in terminal portal venules and hepatic venules have been presumed to be the major sites of pre-and postsinusoidal vascular resistance, whereas the hepatic sinusoids have been compared with capillary beds in other tissues, in which smooth-muscle-like pericytes regulate blood flow. 6 In the sinusoid, endothelial cells and hepatic stellate cells have been identified as the cellular elements most likely to be important in regulation of resistance, 4,7,8 with most data pointing to stellate cells.…”
mentioning
confidence: 99%
“…11 Corresponding to such low blood pressures, intrahepatic portal veins, in spite of their responsibility for conducting and distributing parenchymal blood flow, are invested with only 1 or 2 layers of smooth muscle cells or are even lacking them in places. 12 Furthermore, hepatic sinusoids consist of fenestrated endothelium and incomplete basement membrane different from capillaries. From these facts, it is expected that the location and mechanism of leukocyte margination/emigration in the hepatic vasculature might be different from those in the organs with a high-pressure circulatory system.…”
mentioning
confidence: 99%